Reading of patient case notes by year-one student nurses during clinical practice in a Malaysian Teaching Hospital / Ambika Deavy P. Krishnan Kutty Menon - Ambika Deavy, P. Krishnan Kutty Menon (2017)
This qualitative case study investigated how novice year-one student nurses learned to read and interpret their professional text, the Patient Case Notes (PCN) written by members of the multidisciplinary health team in the deliverance of safe patient care. Student nurses are expected to read PCN as they enter their workplace community of practice for clinical practice. Literature provides evidence on the significance of the PCN in ensuring safe care for patients. However, there appears to be only a cursory mention of student nurses learning to read the PCN during their initial Clinical practice in their workplace. Thus the aim of the study is to contribute to the field of knowledge specifically at understanding the novices’ initial textual experiences, the literacy practices associated with the reading of the PCN and their interpretive efforts. The sources of data included observation field notes, official documents, and semi-structured interviews with eight key participants and informed individuals. Lave and Wenger’s (1991) theory formed the theoretical framework of the study as it provided the lens to investigate and understand the nature of the novices’ reading within the context of a specific workplace community of practice, namely the hospital setting. Data analysis and findings were thus discussed in relation to Lave and Wenger’s (1991) theory. The findings revealed the complexity of using the authentic PCN for the novice users when they transitioned into their workplace for clinical practice. The complexity pointed to a gap in their in-class and workplace literacy practices. Findings also showed that the novices’ reading and interpretive efforts of the PCN were facilitated through their legitimate peripheral participation in routine nursing events, pedagogical mechanisms of the hospital and nursing college, individual competence of expert members of their Community of Practice, their own learning strategies and shared knowledge with their peers. The insights from the study also contribute to existing literature in the areas of curricula practices for novices’ transitioning into their workplace Communities of Practice for learning the practice of nursing specifically in acquiring the literacy practices of their discourse community related to the reading of the PCN.